Egalitarianisme Fiqh Muâmalah dalam Sistem Ekonomi Islam - Maksum, Moh. Asra (Program Pascasarjana UIN Sunan Ampel Surabaya, 2012)
This paper tries to explore the fact that transaction constitutes the most important aspect of Islamic jurisprudence, commonly called fiqh. The paper tries to deal with this aspect in terms of the legal thought of Islam and relates it with the modern concept of egalitarianism. It argues that although egalitarianism becomes the most important value in the legal thought of Islamâas it is clear in the concept of transactionâthe tension toward establishing this value has not been easy. This paper hence, does not deal merely with the normative aspect of the value, but also the history behind its establishment. In a way, the paper understands that both the concept of transaction in Islamic legal thought and the concept of egalitarianism share common grounds in that both are about equality, justice, right and obligation. Equality is strongly upheld in Islamic legal thoughts so much so that it is considered as the most driving legal concept in Islamic economics. Hence, the paper partly argues that the characteristic of Islamic economics is equality, nothing else.